A biomimetic synthetic nanofiber-based model for anterior cruciate ligament regeneration - Adeoye, Abass Ojo; Mukasheva, Fariza; Smatov, Smail; Khumyrzakh, Bakhytbol; Kadyr, Sanazar; Shulgau, Zarina; Erisken, Cevat (Frontiers in Bioengineering and Biotechnology, 2022)
Reconstructed ACL cannot completely restore its functions due to absence of physiologically viable environment for optimal biomaterial-cell interaction. Currently available procedures only mechanically attach grafts to bone without any biological integration. How the ACL cells perform this biological attachment is not fully understood partly due to the absence of appropriate environment to test cell behavior both in vitro and in vivo. Availability of biomimetic models would enable the scientists to better explore the behavior of cells at health and during tissue healing. In this study, it is hypothesized that the collagen fibril diameter distribution in rat ACL changes from a bimodal distribution in the healthy ACL to a unimodal distribution after injury, and that this change can be mimicked in synthetic nanofiber-based constructs. This hypothesis was tested by first creating an injured rat ACL model by applying a mechanical tensile force to the healthy ACL tissue until rupture. Secondly, the collagen fibril diameter distributions of healthy and injured ACL tissue were determined, and polycaprolactone (PCL) constructs were created to mimic the distributions of collagen fibrils in healthy and injured tissues. Findings reveal that the fiber diameter distribution of aligned bimodal PCL constructs were similar to that of the collagen fibrils in native ACL tissue. This study is significant because suggested bimodal and unimodal fibrous model constructs, respectively, represent a healthy and injured tissue environment and the behavior of ACL cells cultured on these constructs may provide significant input on ACL regeneration mechanism.